Students’ Perception on EFL Speaking for English Teacher - Agus Rofi'i; Eka Nurhidayat (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2019)
This study aims to increase presentation skills in English and one of the communication tools to convey ideas and feelings to others. Through language, people can be interconnected, learn from each other, and improve their intellectual abilities. One of the abilities demanded by alumni of English Education Study Programs is the ability to communicate in English presentation. Based on the experience of researchers while teaching, there are still students who are unable to present in English Presentation. The research activity is done by teaching process on the classroom and it is happened on second semester students of the English Education Study Program. The program is done by teaching and practicing them the speech, making presentation, speech delivery and being moderator. This English presentation method is applied to students majoring in English and this research uses descriptive qualitative method to describe in speaking by using English Presentation.  DOI: 10.26905/enjourme.v4i2.3720